ARBITRAGE, AN EFFICIENT ALTERNATIVE FOR RESOLVING TRADE DISPUTES IN ALBANIA, COMPARATIVE OVERVIEW WITH AUSTRIA, ARMENIA, ARGENTINA AND BULGARIA. - Ma, Ana Rushiti (IJRDO - Journal of Social Science and Humanities Research, 2022)
Arbitration is a new form of dispute resolution in the commercial field in Albania. Economic development has led many international companies to invest in Albania. This topic will focus on the concept of arbitration as the public interest in recognizing this new form of dispute resolution is broad, but what never changes is the argument as to why we turned to arbitration. The parties set the arbitral tribunal in motion and as such have the burden of proof to prove that their claims are based on facts and evidence. Of particular importance in this paper will be the advantages and disadvantages of arbitration as a way of resolving disputes. Another special aspect where we need to dwell will be the contribution of national courts in resolving arbitration disputes. This paper will deal extensively with the place it occupies in Albanian legislation. An important place of this paper will be the analysis of practical cases as a way of combining theory and practice. It would be of particular interest to make comparisons between Albanian legislation and Austria, Argentina, Armenia and Bulgaria. The reason for this comparison is to bring about a radical change in the resolution of trade disputes through arbitration. An important place of this paper will be the analysis of practical cases as a way of intertwining theory and practice. It would be of particular interest to make comparisons between Albanian legislation and Austria, Argentina, Armenia and Bulgaria. The reason for this comparison is to bring about a radical change in the resolution of trade disputes through arbitration. An important place of this paper will be the analysis of practical cases as a way of intertwining theory and practice. It would be of particular interest to make comparisons between Albanian legislation and Austria, Argentina, Armenia and Bulgaria. The reason for this comparison is to bring about a radical change in the resolution of trade disputes through arbitration.Albania needs the recognition of arbitration as an opportunity to resolve the dispute as every action affects the image of the company but also of our country. Models from different countries will help us bring a new but above all efficient approach